2021
DOI: 10.1007/s12559-021-09829-6
|View full text |Cite
|
Sign up to set email alerts
|

Design and Deployment of an Image Polarity Detector with Visual Attention

Abstract: Embedding the ability of sentiment analysis in smart devices is especially challenging because sentiment analysis relies on deep neural networks, in particular, convolutional neural networks. The paper presents a novel hardware-friendly detector of image polarity, enhanced with the ability of saliency detection. The approach stems from a hardware-oriented design process, which trades off prediction accuracy and computational resources. The eventual solution combines lightweight deep-learning architectures and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 43 publications
1
12
0
Order By: Relevance
“…This section illustrates the results of the experiments performed in the three test scenarios. According to our previous findings [38] we observed that moving the same architecture from the Desktop to the embedded platform has negligible impact on the detection accuracy, while it mostly affects speed and memory footprint. Therefore, in Sections 5.1-5.3 we first illustrate, for each scenario, our achievements using the Desktop platform and, then, in Section 5.4, we analyze the impact of deploying T-RexNet on the Jetson Nano.…”
Section: Resultssupporting
confidence: 54%
See 2 more Smart Citations
“…This section illustrates the results of the experiments performed in the three test scenarios. According to our previous findings [38] we observed that moving the same architecture from the Desktop to the embedded platform has negligible impact on the detection accuracy, while it mostly affects speed and memory footprint. Therefore, in Sections 5.1-5.3 we first illustrate, for each scenario, our achievements using the Desktop platform and, then, in Section 5.4, we analyze the impact of deploying T-RexNet on the Jetson Nano.…”
Section: Resultssupporting
confidence: 54%
“…TensorTRT can adopt different data sizes when deploying a network: standard floating-point representation (FP32), half-precision floating point (FP16) and 8-bit integer representation (INT8). The experiments were conducted with the FP16 format since this provides a good trade-off between accuracy and power consumption [38]. In addition, the results proved that FP16 is indeed sufficient to reach good frame rates using Jetson Nano.…”
Section: Deploymentmentioning
confidence: 98%
See 1 more Smart Citation
“…Beyond the comparison of these compact architectures inspired to their larger counterparts, few works that empirically study or propose different approaches to tackle the limitations posed by embedded devices have also been published in related task such as polarity detection from visual data [ 26 , 27 ], speech recognition [ 28 ] and conversational agents [ 29 ]. In addition, the trade-off between computational cost and generalization performance for sentiment analysis was studied in [ 30 , 31 ], but the focus was not on the deployment of the solution.…”
Section: Related Workmentioning
confidence: 99%
“…Given the above, online cyber social networks can tell us what people are talking about right now and what is happening in the world. Especially, identifying the polarity of users in various fields on cyber social networks, has also become a popular and useful research topic (see [1,2,3,4,5,6,7,8,9,10,11]).…”
Section: Introductionmentioning
confidence: 99%